Violence on the Job: Identifying Risks and Developing Solutions. 1996
DOI: 10.1037/10215-009
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence in federal agencies.

Abstract: Violent encounters that result in time loss from work or workers' compensation claims may be particularly good benchmarks for tracking workplace violence. Tracking is possible because such events are workplace related, records are available and convenient to study, cases of serious health outcomes are defined already, useful information is available on the occurrence of the event, and individual records are relatively complete. Such records can offer useful impressions about the peculiarities in the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Similarly a brief review of the psychological and behavioral literature on workplace violence indicates considerable research published since 1994 (see e.g., VandenBos & Bulatao, 1996), with virtually no studies cited in the literature prior to 1991. Topics include issues of violence in particular work settings (e.g., Dignam & Fagan, 1996;Freeman, Fox, Burr, & Santasine, 1996;Shazer, 1996), causes of workplace violence (e.g., Baron & Neuman, 1996), and legal issues (Bernat, 1994;Painter, 1991). Various articles have explored prevention and intervention strategies (e.g., Bush & O'Shea, 1996;Nicoletti & Spooner, 1996), but no evaluation research was found examining the eectiveness of prevention and intervention models in responding to and reducing the incidence of targeted violence in the workplace.…”
Section: Workplace Violencementioning
confidence: 99%
“…Similarly a brief review of the psychological and behavioral literature on workplace violence indicates considerable research published since 1994 (see e.g., VandenBos & Bulatao, 1996), with virtually no studies cited in the literature prior to 1991. Topics include issues of violence in particular work settings (e.g., Dignam & Fagan, 1996;Freeman, Fox, Burr, & Santasine, 1996;Shazer, 1996), causes of workplace violence (e.g., Baron & Neuman, 1996), and legal issues (Bernat, 1994;Painter, 1991). Various articles have explored prevention and intervention strategies (e.g., Bush & O'Shea, 1996;Nicoletti & Spooner, 1996), but no evaluation research was found examining the eectiveness of prevention and intervention models in responding to and reducing the incidence of targeted violence in the workplace.…”
Section: Workplace Violencementioning
confidence: 99%
“…According to Kingma (2001), healthcare workers are 16 times more likely to experience violent assaults than any other service workers. In a review of violence in federal agencies based on 1993 Office of Workers Compensa-tion Plan data, Freeman, Fox, Burr and Santasine (1996) found that the US Department of Veterans Affairs (VA) had one of the highest rates of fatal and nonfatal assaults of all federal agencies and that the targets tended to be nursing staff and police. Thus, what is clear is that the healthcare service delivery interface is a fertile one for hostile interactions.…”
Section: Introductionmentioning
confidence: 99%